LEI, J.Q., CAI, J., ZHOU, S.D. & HE, X.J. (2023) Ligusticopsis miyiensis (Apioideae, Apiaceae), a new combination from China revealed by morphological and molecular evidence. Phytotaxa 591 (4): 273–282. - Lei, Jia-Qing; Cai, Jing; Zhou, Song-Dong; He, Xing-Jin (Phytotaxa, 2023)
N/A